Towards redefinition of an actus reus of rape in Malaysia / Husmarudin Husin, Rozaimah Adnan, Martha Vims - Husin, Husmarudin; Adnan, Rozaimah; Vims, Martha (2005)
This study seeks to determine the need of reviewing the definition of an actus reus or physical elements of rape in Malaysia. As a definition stand under section 375 of the Penal Code (hereinafter will be referred as PC), it is noted that the actus reus of rape consists of two elements namely sexual intercourse and without consent. In this study we tiy to prove that the definition and scope of actus reus of rape in our current Penal Code is out dated and not in line with common law countries such as Australia and New Zealand. As the time goes by, this traditional definition of rape under section 375 of the PC is not enough to cover the advance sexual conduct made by our society these days. For the puipose of this study, we confine our scope to a definition of sexual intercourse, its nature, scope, application and current legal development and in what side it different from common law countries. There are several techniques that we had used in collecting the data for the puipose of our study such as conducting an interview people who are veiy expert in this field like police officer, SUHAKAM, practiced lawyer and lecturers from school of law. Besides that, we also used the secondary data which we obtained from reading case law, analysis of statutory law and legal reasoning (ratio decidendi) used by judges in making their judgment. This study signifies that there is a loop holes in our PC with regards to the actus reus and therefore needs to be amended.